PENGARUH FUNGSI KELUARGA TERHADAP PERILAKU MEROKOK REMAJA DI DESA WALUYOREJO KECAMATAN PURING KABUPATEN KEBUMEN - Bibit Priyatin; marsito -; sarwono - (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2009)
Teenagers have big influence on clean and health lifestyles such as no smoking lifestyle. That is why; the family function has an important role on controlling the smoking behavior of the teenagers. This research is to evaluate the impact of family function toward adolescent smokers behavior in countryside of waluyorejo, sub district puring, regency kebumen, central java. This research is a survey analytic correlation with the cross sectional approach to find out the family function influence that divided into 5 family function; affective, social function, economic function, reproductive function, and health function correlated with the smoking behavior of Adolescent Cigarette Behavior In Countryside of Waluyorejo, Sub district Puring, regency Kebumen, Central Java. There are 83 adolescents as the samples in this research. They are stil life with they parent in Countryside of Waluyorejo, Sub district Puring, regency Kebumen, Central Java and they are smokers. The sampling technique was done by using the cluster purposive sampling. The data analyses used were univariate and bivariate with chi square test. The research found that the family function influenced the smoking behavior of the adolescent in Countryside of Waluyorejo, Sub district Puring, regency Kebumen, Central Java. Are social function (p value = 0.020), economic function (p value = 0.000), and health function (p value = 0.031). Because of this reason, it is necessary for the parents or family to have a strong commitment to apply their function as the family to control their teenage children and they can also consider their teenage children development characteristic. Community Nurse has a role on giving suggestion to the parents so that they can do their exact function as the family and give the right and needed information for their teenage children appropriate with their children development stages. Keywords: family function, teenagers’ smokers